Optimization and analysis of force field parameters by combination of genetic algorithms and neural networks - Hunger, Jens; Huttner, Gottfried (Journal of computational chemistry, 1999)
In search of a force field description for tripod metal templates, tripodM [tripod=RC(CH2X)(CH2Y)(CH2Z); X, Y, Z=PR′R″] force field parameters, p, were optimized by the use of genetic algorithms (GA) with...
Gesehen am 15.03.2018